CLINICAL EFFECTIVENESS OF PREOPERATIVE VACUUM THERAPY IN THE CORRECTION OF PECTUS EXCAVATUM IN ADOLESCENTS USING THE D. NUSS THORACOPLASTY TECHNIQUE - Mirdadayeva Dilfuza Davlatovna; Mirdadayev Jamshid Farkhodovich (Modern American Journals, 2026)
Pectus excavatum is the most common congenital deformity of the chest wall, accounting for up to 85–90% of all thoracic deformities. In addition to cosmetic concerns, this condition may cause functional impairment of the respiratory and cardiovascular systems, particularly during adolescence. Surgical correction using the D. Nuss thoracoplasty technique is widely accepted as the gold standard; however, it is often associated with significant postoperative pain, prolonged rehabilitation, and the risk of metal bar displacement.
Keywords: Pectus excavatum; adolescents; preoperative vacuum therapy; D. Nuss thoracoplasty; chest wall deformity; surgical outcomes